Comparison of the effectiveness of online supportive parenting intervention (SPACE) and timid to tiger program (FTTT) on childhood anxiety disorders and family accommodation with samples of Iranian parents - Ghodrat, Mohaddeseh Sadat; Aghebati, Asma; Asgharnejad Farid, Ali Asghar; Shirazi, Elham (Frontiers in Psychology, 2022)
Studies have supported the effectiveness of the From Timid to a Tiger (FTTT) and Supportive Parenting for Anxious Childhood Emotions (SPACE) program in reducing childhood anxiety. This study is the first to compare the effectiveness of the two programs in the treatment of childhood anxiety disorder and reducing family accommodations levels. Parents of children aged 6 to 9 (n = 49, 49% boys) were randomly allocated to either FTTT (n 26) or SPACE (n = 23) groups, and each attended ten online sessions following the manuals of the interventions. Throughout the study, 9 participants dropped out, resulting in a total of 49 participants, and we performed statistical analyses based on data from these 49 participants. The assessment took place pre- and post-treatment and at a ten-week follow-up on parent-rated child anxiety and family accommodation measures. Analyses of variance (repeated measures) and gain scores were conducted to examine the data. The results indicated that both treatments approaches produced significant reductions in outcome measures, and the post-treatment gains of both treatments were maintained at a ten-week follow-up, though when considering the mean differences and effect sizes across the assessment scores and between groups, overall, the FTTT was significantly more effective in reducing child anxiety scores and family accommodation levels. Our results demonstrated that FTTT significantly outperformed the SPACE program in reducing childhood anxiety problems and family accommodation levels.